Virtual, augmented and mixed reality. Systems and applications : 5th International Conference, VAMR 2013, Held as Part of HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part II - Shumaker, Randall (Lecture Notes in Computer Science, 2013)
Here is the second of a two-volume set (LNCS 8021 and 8022) that constitutes the refereed proceedings of the 5th International Conference on Virtual, Augmented and Mixed Reality, VAMR 2013, held as part of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 88 contributions included in the VAMR proceedings were carefully reviewed and selected for inclusion in this two-volume set. The papers included in this volume are organized in the following topical sections: healthcare and medical applications; virtual and augmented environments for learning and education; business, industrial and military applications; culture and entertainment applications.